Supernumerary embryos, do they show the cycle success in a fresh embryo transfer? A retrospective analysis. (2nd December 2021) - Aslan, Kiper; Kasapoglu, Isil; Cakir, Cihan; Avci, Berrin; Uncu, Gurkan
Abstract: Objective: To determine the predictive value of cryopreserved embryos during single fresh blastocyst transfer Methods: This retrospective cohort study was conducted at a tertiary university hospital ART center. Patients who underwent a single fresh blastocyst transfer were selected from the electronic database. Patients with diminished ovarian reserve, uterine pathology, advanced age (>40 years) were excluded from the study. Patients were divided into two groups. Group A consisted of patients with only one available embryo for the fresh transfer. Group B consisted of patients with cryopreserved embryos apart from the fresh transferred embryo. Demographic and embryology parameters, pregnancy results were compared. Results: Demographic values, ovarian reserve parameters were comparable between groups. The number of the picked-up oocyte, metaphase-2 oocyte, and two-pronucleus embryo was lower in Group A. Positive pregnancy rates were two-fold higher in Group B (23.4% vs. 50.9% p  < .01). Pregnancy results did not change depending on the number of cryopreserved embryos in Group B. Conclusion: According to our results, the presence of cryopreserved embryos results in higher pregnancy rates in patients with fresh blastocyst embryo transfer independent from the woman's age and ovarian reserve. Thus, these results may help us to predict the implantation rate before embryo transfer.